Blood-CSF-barrier dysfunction is a marker for encephalitic involvement in patients with aseptic meningitis/meningoencephalitis - Hoyer, Carolin; Eisele, Philipp; Ebert, Anne; Schneider, Sven; Gass, Achim; Fatar, Marc; Szabo, Kristina; Alonso, Angelika (Clinical and diagnostic virology, 2016)
Background - The term “aseptic meningitis” encompasses cases of meningitis with negative bacterial CSF culture, which predominantly are of viral etiology. While the clinical course is usually benign, complications such as encephalitic involvement resulting in a more severe clinical course may occur. Dysfunction of the blood-brain-barrier (BBB), which is a prerequisite for viral entry into the brain parenchyma, can be approximated using the CSF/serum albumin ratio, readily obtainable in routine CSF analysis. - Objecitves - Analysis of CSF patterns in patients with aseptic meningitis/meningoencephalitis with a focus on BBB dysfunction as a marker for encephalitic involvement. - Study design - Retrospective chart review of patients admitted to our hospital between 2004 and 2016 with a diagnosis of aseptic meningitis/meningoencephalitis. - Results - Patients with aseptic meningitis displaying clinical, MR-tomographic or electroencephalographic signs of encephalitic involvement were significantly older than patients without these features (47.4 vs. 35.5 yrs., p=0.002). In patients with meningoencephalitis, CSF analysis revealed a more severe disruption of BBB, approximated by the CSF/serum albumin ratio (p=0.002). Compromised BBB function correlated positively with length of hospitalization (p=0.007), indicative of a more severe clinical course. The number of CSF lymphocytes was found to predict the severity of the BBB disruption, which additionally was more frequently observed when herpesviridae were identified as infectious agents. - Conclusions - We suggest that the CSF/serum albumin ratio as an estimate for BBB function should be attended to in the evaluation of patients with aseptic meningitis. Severe BBB dysfunction, older age and infection with herpesviridae appear to raise the risk for encephalitic involvement.
Gesehen am 28.05.2019
Available online 6 October 2016